Sustainable hydrogen-rich syngas from steam reforming of bio-based acetic acid over ZnO and CeO2–ZnO supported Ni-based catalysts. Issue 62 (15th October 2020) - Luo, Shan; Sun, Fazhe; Fu, Peng; Sun, Qi; Wang, Jianlin
Abstract : Variation of hydrogen-rich syngas from steam reforming of bio-based acetic acid over Ni/ZnO and Ni/CeO2 –ZnO catalysts was assessed. Abstract : Sustainable hydrogen-rich syngas from steam reforming (SR) of bio-based acetic acid over ZnO and CeO2 –ZnO supported Ni-based catalysts was studied by means of a bench-scale fixed-bed unit combined with NDIR/TCD techniques. The effects of Ni/ZnO catalysts with different nickel loadings (5–15%), temperature ( T = 500–900 °C), steam to carbon molar ratio (S/C = 1–5) and weight hourly space velocity (WHSV = 3–7 h −1 ) on SR of acetic acid were explored. In addition, the influence of CeO2 addition on the catalytic performance was assessed to investigate the improvement effect of Ce as a promoter on the catalytic activity. As the nickel loading increased from 5 to 15%, the H2 yield increased significantly from 31.0 to 51.0% with a growth rate of 64.5%, while the CO yield first decreased from 31.6 to 27.7% and then increased to 35.7%. Between 500 and 900 °C, the yields of H2 and CO first increased and then decreased, corresponding to the peak yields of 51.0% and 35.7% at 800 °C, respectively. S/C gave a similar trend of H2 yield to the T, while the CO yield continued to decrease with increasing S/C from 1 to 5. The H2 yield gradually decreased from 54.1 to 28.7% as the WHSV increased, while the peak value of CO yield was 35.7%, corresponding to WHSV = 5. The addition of 25 wt% CeO2 to the Ni/ZnO catalyst with a nickel loading of 15% improved the H2 yield from 51.0 to 74.0% when reforming acetic acid under the optimal operating conditions of T = 800 °C, S/C = 3 and WHSV = 5 h −1 . The CO yield was reduced from 35.7 to 33.2%, and the corresponding H2 /CO ratio increased from 2.9 to 4.5. The excellent catalyst stability was obtained in the SR of acetic acid using Ni/CeO2 –ZnO catalyst. H2 yield was reduced from 76.0 to 73.5% with a decrease of 3.4%, while CO yield increased from 32.1 to 41.3% with a growth rate of 28.7% within 15–360 minutes.